EES Based Software Design as a Thermal Performance Evaluation Tool of Coal-fired Steam Power Plant (STUDY CASE: PLTU JATENG 2 ADIPALA - Halim Dwi Gunawan - Nim: 13113120 , Muhammad
Evaluation program of continuous thermal performance data is one of the efforts for a coal steampowered electric generator can operate with optimum conditions. In this research a software would be designed as a tool for evaluation of thermal performance. The design of the software was focused on evaluation of thermal performance of PLTU Jateng 2 Adipala at 100% TMCR condition. The thermal performance parameters to be reviewed were the efficiency of steam generators, GTHR, GPHR, and NHHR based on HHV and LHV. The software was designed using the EES program. The calculation step of each thermal performance parameter was based on ASME PTC 4.1 for steam generator test and ASME PTC 6 for steam turbine testing. Research activities undertaken included performance guarantee data collection as well as thermal data of test results, thermal performance calculations using software that had been designed, validation of thermal performance calculation results and comparison of thermal performance parameters on performance guarantee data with thermal performance calculation of operating data of test results with factors correction. After further analysis, the efficiency values of steam generator, GPHR, GTHR, and NPHR based on HHV and LHV, without either correction factor or correction factor indicated that the parameters in performance guarantee were achieved.